2019
DOI: 10.1186/s12989-019-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

ROS promote epigenetic remodeling and cardiac dysfunction in offspring following maternal engineered nanomaterial (ENM) exposure

Abstract: Nano‐titanium dioxide (nano‐TiO2) is one of the most prevalently utilized ENMs. However, little is known regarding the ramifications that maternal inhalation exposure during gestation can have on growing progeny. Mitochondrial bioenergetics are critical for the maintenance of sufficient ATP for cardiac contractile function and data suggest that ENM exposure can cause deficits in this important mitochondrial role. Further, ENM inhalation exposure has been associated with an increase in mitochondrially‐derived r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 68 publications
0
26
0
Order By: Relevance
“…We, and others, have identified that maternal exposures to metallic and carbonaceous ENM during gestation can initiate developmental onset of disease within the maturing fetus. In laboratory studies, young and adult offspring have been reported to exhibit coronary dysfunction [33][34][35][36][37][38], vascular perturbations [38,39], negative reproductive health outcomes [40][41][42], and neurological outcomes [43][44][45] after maternal inhalation of engineered nanomaterials during pregnancy. It is also plausible that these findings represent a snapshot of time, wherein the particles reach the fetal tissues within 24 h of exposure but are removed from the fetal circulation prior to birth.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have identified that maternal exposures to metallic and carbonaceous ENM during gestation can initiate developmental onset of disease within the maturing fetus. In laboratory studies, young and adult offspring have been reported to exhibit coronary dysfunction [33][34][35][36][37][38], vascular perturbations [38,39], negative reproductive health outcomes [40][41][42], and neurological outcomes [43][44][45] after maternal inhalation of engineered nanomaterials during pregnancy. It is also plausible that these findings represent a snapshot of time, wherein the particles reach the fetal tissues within 24 h of exposure but are removed from the fetal circulation prior to birth.…”
Section: Discussionmentioning
confidence: 99%
“…We, and others, have identi ed that maternal exposures to ENM during gestation can initiate developmental onset of disease within the maturing fetus. In laboratory studies, young and adult offspring have been reported to exhibit coronary dysfunction [40,41,42,43,44,45], vascular perturbations [27,45], reproductive consequences [46,47,48,49,50], and neurodevelopmental delays [51,52] after maternal inhalation of engineered nanomaterials during pregnancy. Therefore, particle deposition, and likely particle accumulation and retention, impact offspring health after birth and into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis showed that nano-TiO 2 exposure via different routes tend to reduce the cardiac output albeit the effect depends on the life stage and the genetic background ( Figure 1C). Thus, fetal mice (prenatally exposed to ≈10 mg m −3 of nano-TiO 2 [54,59] ) showed negligible change in cardiac output. In adult isogenic [59] and heterozygous mice, [56] nano-TiO 2 caused more significant increased cardiac output, whereas in adult wild type and MiRNA-378a knockout mice the cardiac output notably decreased in response to nano-TiO 2 inhalation ( Figure 1).…”
Section: Circulatory and Cardiovascular Systemmentioning
confidence: 96%
“…[64,65] The cardiac contractile dysfunction in the offspring of mice gestationally exposed to nano-TiO 2 was a result of the oxidative stress and inflammation in the heart as well as the direct effects on the fetal vasculature. [59,65]…”
Section: Circulatory and Cardiovascular Systemmentioning
confidence: 99%